Thermodynamics of quark matter with a chiral imbalance - Farias, Ricardo L. S.; Duarte, Dyana C.; Krein, Gastão [UNESP]; Ramos, Rudnei O. (American Physical Society (APS), 2016)
We show how a scheme of rewriting a divergent momentum integral can conciliate results obtained with the Nambu-Jona-Lasinio model and recent lattice results for the chiral transition in the presence of a chiral imbalance in quark matter. Purely vacuum contributions are separated from medium-dependent regularized momentum integrals in such a way that one is left with ultraviolet divergent momentum integrals that depend on vacuum quantities only. The scheme is applicable to other commonly used effective models to study quark matter with a chiral imbalance, it allows us to identify the source of their difficulties in reproducing the qualitative features of lattice results, and enhances their predictability and uses in other applications.